Cross-dimensional electron-phonon coupling in van der Waals heterostructures - Miao-Ling Lin (Nature Portfolio, 2019)
The strength of electron-phonon coupling can be directly probed by Raman spectroscopy. Here, the authors use low-frequency Raman spectroscopy to unveil the existence of a strong cross-dimensional coupling between the bulk-like layer-breathing phonons in an hBN/WS2 heterostructure and the electrons localized within its few-layer WS2 constituent.